Outcomes of Adults With Relapsed/Refractory Acute Myeloid Leukemia Treated With Venetoclax Plus Hypomethylating Agents at a Comprehensive Cancer Center - Tenold, Matthew E.; Moskoff, Benjamin N.; Benjamin, David J.; Hoeg, Rasmus T.; Rosenberg, Aaron S.; Abedi, Mehrdad; Tuscano, Joseph M.; Jonas, Brian A. (Frontiers in Oncology, 2021)
Relapsed/refractory acute myeloid leukemia (AML) is a devastating disease with a poor prognosis and represents a major unmet medical need. We report on a real-world academic center experience of treating 25 patients with relapsed/refractory AML using venetoclax in combination with decitabine or azacitidine, which is not otherwise widely evaluated in the current literature. Our patients come from a large, socioeconomically and geographically diverse area including the majority of Northern California. Most had ELN Adverse Risk (52%) or Intermediate Risk (44%) AML, and most had an ECOG Performance Status of 1 (64%). Over half (52%) had prior hypomethylating agent exposure, and 40% had Secondary AML. We observed an overall response rate of 52%, with eight patients (32%) achieving composite complete remission. Median overall survival was 5.5 months, and for patients achieving composite complete remission this was 21.6 months. One-year estimated overall survival was 38%. Three patients were able to proceed directly to stem cell transplant for consolidation, and all three were alive at last follow-up, ranging 13.8–24.0 months. We found venetoclax in combination with hypomethylating agents to be well tolerated and potentially efficacious in securing long-term remissions for patients with relapsed/refractory AML.